Analyse der Auswirkungen verschiedener agrarpolitischer Rahmenbedingungen auf die Rentabilität der Grünlandwirtschaft in Wasservorranggebieten mit Hilfe eines Betriebsplanungsprogramms; Analysis of the Impacts of Different Agrarian Policy Scenarios on the Profitability of Grassland Management in Water Protection Areas by Use of a Farm Planning Programme - Manfred Bathke (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– The present study is based on micro-simulations on the farm level (7 dairy farms in Lower Saxony). It shows the effect of transformation of livestock premiums in hectare premiums on the profitability of grassland management. The following scenarios were analysed: Introduction of a grassland premium (77 exteuro/ha), increase of the grassland premium to 179 exteuro/ha and abolition of the maize premium, uniform area premium (307 exteuro/ha), combination model (crop premium 307 exteuro/ha, grassland premium 205 exteuro/ha, dropping of all animal premiums except for the milk and bull premiums). The calculations show, that a grassland premium of 77 exteuro/ha would not lead to any considerable adjustment reactions. The simultaneous dropping of the maize premium and the increase in the grassland premium (179 exteuro/ha) would lead to small advantages for the grassland economy. A uniform hectare premium (307 exteuro/ha) would lead to strong income redistributions between the examined enterprises (up to +/-50 exteuro/ha). Loss of grassland on favourable sites would continue. On unfavourable sites grassland fallow would considerably increase. The combination model would lead to less serious income redistributions. Taking along effects on marginally used grassland and the rise of land rental prices would be less pronounced. Grassland fallow will not have any significant effects on the quality of the groundwater recharge. With regards to nature conservation aims substantial problems will arise, since the extensive use of pasture will not be partially financed any more through animal premiums.
Keywords: 330; Weidewirtschaft; Gewässerschutz; Agrarpolitik; Landwirtschaftliche Betriebsform